Forced migration under conditions of high social vulnerability of the population of Ukraine - Bil, Mariana (Migration & Law, 2023)
The forced migration of the population of Ukraine in the context of high social vulnerability is researched in the article. The aim of the article is actualization of the problematics of the forced migration researches in the context of social vulnerability of the population; determination of the actual problems of regulating the forced migration of the population of Ukraine in today’s conditions and through the prism of planning the priorities of post-war recovery. The results of the research are theoretical generalizations about the essence of forced migration and it’s interrelation to the population social vulnerability. A retrospective analysis of the migration of the population of Ukraine confirmed that forced migration was characteristic of the second and third migration waves of the 20th century. Faced with forced migration in 2014, legal, organizational and other mechanisms for regulating these processes were formed in independent Ukraine. However, given the scale of forced displacements in 2022, they should be applied more comprehensively and effectively. The analysis of trends in forced migration since 2022 rejected the hypothesis about the high potential of the population re-emigration, that was widespread in the first half of the year of the Russian invasion. Significant migration losses in the conditions of a demographic catastrophe determine the urgent need to regulate forced migration. The analysis of the projects and measures of the Recovery Plan of Ukraine related to the regulation of forced migration and the reduction of the population social vulnerability confirmed their overly extensive and unsystematised list and the risks of high formalism during implementation, taking into account the low political culture in Ukraine. In this regard, the basic directions of state policy are proposed that are support for internally displaced persons, stimulation of re-emigration to Ukraine and effective use of migration capital by directing migrants’ remittances for investment purposes, transfer of acquired rights from social insurance upon return.